Fuzzy anti-windup scheme for practical control of point-to-point (Ptp) positioning systems - Wahyudi, Wahyudi; Albagul, Abdulghani (Penerbit UTM Press, 2005)

(untitled)
The Positioning Systems Generally Need A Controller To Achieve High Accuracy, Fast Response And Robustness. In Addition, Ease Of Controller Design And Simplicity Of Controller Structure Are Very Important For Practical Application. For Satisfying These Requirements, Nominal Characteristic Trajectory Following (NCTF) Controller Has Been Proposed As A Practical PTP Positioning Control. However, The Effect Of Actuator Saturation Cannot Be Completely Compensated Due To Integrator Windup Because Of Plant Parameter Variations. This Paper Presents A Method To Improve The NCTF Controller For Overcoming The Problem Of Integrator Windup By Adopting A Fuzzy Anti-Windup Scheme. The Improved NCTF Controller Is Evaluated Through Simulation Using Dynamic Model Of A Rotary Positioning System. The Results Show That The Improved NCTF Controller Is Adequate To Compensate The Effect Of Integrator Windup.